The Polish contribution to financial econometrics. A review of methods and applications - Osińska, Magdalena (Polski wkład w ekonometrię finansową. Przegląd metod i zastosowań, 2016)
Since 1982 the term “financial econometrics” has been present in the enormous literature that covers both methodologies and empirical analyses of the processes observed on the financial markets. The purpose of the presented paper is to indicate the milestones in financial econometrics and their usefulness and to show the contribution of the research from Poland into its development. ‘Pure’ financial econometrics methods are of special interest. The paper is directed at reviewing the recent methodologies and their applications. We focused on the contribution of Polish researchers into financial econometrics over the years, considering both the methodology and the applications. Some of the indicated publications are cited quite often, including international quotations, others are not very popular due to the language of the publication or the local reach of the journal, although many of them can be considered in line with the achievements that are presented in international empirical publications
Ekonometria = Econometrics, 2016, Nr 4 (54), s. 9-35
Keywords: financial econometrics; volatility models; risk measures; extreme value theory; microstructure; behavioral information; ekonometria finansowa; modele zmienności; miary ryzyka; teoria wartości ekstremalnych; mikrostruktura; informacja behawioralna